Analisis Penerapan Manajemen Keselamatan dan Kesehatan Kerja pada Proyek Konstruksi - Ganjar Jojon Johari; Azis Muslim (Jurnal Konstruksi, 2025)
The construction sector carries a high risk of workplace accidents, making the implementation of Occupational Health and Safety (OHS) management essential to ensure worker safety and support smooth project execution. This study aims to analyze the extent of OHS management implementation in the Rancabango Hotel Construction Project, Garut Regency, and to identify inhibiting factors and control measures. The research applied a descriptive quantitative approach through questionnaires distributed to 65 respondents representing various project roles. Data were analyzed using descriptive statistical methods and the Respondent Satisfaction Index (RSI). The results show that several aspects have been implemented relatively well, including OHS policies (X = 3.17), equipment and machinery inspection (X = 3.4), and workplace cleanliness (X = 3.46), all of which fall into the “Agree” category. However, there remain significant weaknesses in OHS implementation, particularly in accident evaluation (X = 2.15), use of personal protective equipment (PPE) (X = 2.34), and leadership attention to OHS (X = 2.34), which are all categorized as “Disagree.” These factors represent the main obstacles to effective OHS management on the project. As control measures, the study recommends appointing certified OHS officers, improving training and awareness programs, and implementing standard operating procedures (SOPs) for regular accident evaluations. The findings are expected to serve as a reference for enhancing the effectiveness of OHS management in construction projects, thereby reducing potential workplace accidents, improving productivity, and fostering a safer and more sustainable work environment.